MECHANISMS OF DEVELOPMENT OF AXIOLOGICAL COMPETENCES IN STUDENTS (Scientific journal of the Fergana State University, 2024)
In this article, it was determined that it is necessary to develop axiological competences in students, strengthen their need to participate in spiritual-educational events, and widely introduce activities that have a positive effect on the development of axiological competences in them. The importance of their spiritual values, social orientation, ideals, and life strategies in the development of axiological competencies in students is presented in Figure 1, entitled "Mechanism of developing axiological competencies in students". In this mentioned mechanism, spiritual and moral values, cultural traditions; understanding and respecting universal human values ​​and following the values ​​of society; to remain faithful to the continuing traditions; focusing on honesty and humility as the basis of activity. All of the listed values ​​can serve as criteria for assessing the level of students' axiological competences. In order to expand students' outlook, learn educational information, and develop field-related competencies, it is desirable to form axiological competencies expressed by students based on certain pedagogical and conceptual approaches. The implementation of these stages in the development of axiological competencies of students on the basis of pedagogical conditions, didactic principles and approaches is described in detail in Table 1 entitled "Stages of developing axiological competencies in students".